Determination of peripapillary vessel density in optic disc drusen using EDI-OCT and OCT angiography. (August 2020) - Lindberg, Anne-Sofie Wessel; Dahl, Vedrana Andersen; Karlesand, Isabelle; Rueløkke, Lea Lybek; Malmqvist, Lasse; Hamann, Steffen
Abstract: Optical coherence tomography angiography (OCTA) is a rapidly developing technique which generates angiographic images non-invasively. This study proposes a method to determine the vessel density in OCTA scans in general and especially the local peripapillary vessel density. The method produces vessel density heatmaps that contain information about the local vessel density. We apply the method in a small study to demonstrate its applicability and its potential to investigate the influence of local conditions on the vessel density. In the study, we combine information from enhanced depth imaging optical coherence tomography (EDI-OCT) about the location of optic disc drusen (ODD) with information from OCTA about the vessel density. We see a reduction in local peripapillary vessel density in peripapillary sections with a large volume of ODD. Highlights: The developed vessel density heatmaps enables investigation of local vessel density. Large optic disc drusen volume results in low local peripapillary vessel density. Investigation of the impact on vessel density from local anatomic conditions. Multiplexed optical coherence tomography imaging.